The Influence of Curriculum Changes on Learning Methods at SDN Development 9 - Ananda, Mutya; Lestari Simanjuntak, Pitria; Husna, Faradellatul; Melinda, Rida; Adi Putra, M Hafizan; Aslamiah, Aslamiah; Ayu Pratiwi, Diani (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to analyze the impact of curriculum changes on teaching methods at SDN Pengembangan 9. Although curriculum changes are expected to improve the quality of education, their implementation often poses challenges for teachers and students. Using a qualitative approach with a case study method, data were collected through observations, in-depth interviews with teachers, and document analysis related to the curriculum and student learning outcomes. The results of the study indicate that the curriculum change has a significant impact on teaching methods in the classroom. Teachers at SDN Pengembangan 9 faced difficulties in adjusting their teaching methods to meet the demands of the new curriculum, including understanding updated materials and teaching strategies. Some teachers required additional training to effectively implement the curriculum. Furthermore, students also experienced challenges in adapting to these changes, which affected their motivation and learning performance. These findings emphasize that the successful implementation of the new curriculum requires comprehensive support for teachers, including training, guidance, and adequate resources. In conclusion, curriculum changes have the potential to improve the quality of education, but they require effective support strategies to ensure their positive impact can be optimally realized in the primary school environment..